GREEN PUBLIC FINANCIAL MANAGEMENT: INTEGRATING ENVIRONMENTAL METRICS INTO GOVERNMENT BUDGET REPORTING - Rita J D Atarwaman; Nirwana Nirwana; Aini Indirajawati (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
Green Public Financial Management (PPM) is a strategic approach to public financial management that integrates environmental considerations into the entire fiscal policy cycle, particularly in the budgeting and government financial reporting processes. This study aims to systematically examine the concept, framework, and practice of integrating environmental metrics into government budget reporting through a literature review. This study analyzes various scientific publications, international agency reports, and policy documents relevant to the implementation of Green PFM in various countries. The results indicate that integrating environmental metrics, such as carbon emissions, energy efficiency, and natural resource management indicators, into government budget reporting has the potential to improve fiscal transparency, public accountability, and policy consistency between economic development goals and environmental sustainability. However, the implementation of Green PFM still faces several challenges, including limited institutional capacity, the lack of environmental measurement standards integrated with public accounting systems, and the complexity of cross-sector coordination. This study concludes that strengthening the regulatory framework, developing adaptive financial information systems, and improving human resource competencies are essential prerequisites for the successful integration of environmental metrics into government budget reporting. This study is expected to provide a conceptual contribution to the development of public finance policies oriented towards sustainable development.